Enhancing Higher Education Writing Achievement: An Experimental Exploration Of Problem-Based Learning And Technological Integration - Rona Rossa; Elva Zuleni; Riri Marfilinda; Muzayyanah Muzayyanah; Rahmia Tulljanah (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to improve higher education writing achievement through a ground-breaking experimental investigation of problem-based learning and technological integration. Motivated by recognized issues in English education at Adzkia University, where students struggle with weaknesses in paragraph building, idea production, and organizational skills, our research strives to reshape the landscape of writing training. Our study pioneers a unique departure from previous techniques by recognizing instructional methodology and technology as critical elements. Problem-based learning and technological integration emerge as dynamic alternatives, promising a paradigm shift in how writing skills are developed in higher education. The instruments that were used for this research were writing tests. T-test analysis was used in analyzing the data. Our findings from T-test analysis show that students exposed to problem-based learning and technology significantly improve their writing proficiency, exceeding their counterparts in traditional education. In summary, this study drives the conversation on educational technique, asking institutions to embrace the dynamic integration of problem-based learning and technology. The findings not only demonstrate the effectiveness of this novel strategy, but also herald a new age in higher education in which writing prowess becomes an empowered manifestation of student accomplishment.